The Influence of Flavor on The Purchase Decision Of Bakpia Mutiara Jogja - Pratama, Galuh (Gastronomy Tourism Journal, 2020)
The purpose of this study is to determine the influence of flavor on the purchasing decision of Bakpia Mutiara Jogja. This study uses a quantitative approach. The population of this research are consumers who have bought bakpia at Bakpia Mutiara Jogja store. The sampling technique uses purposive sampling. The sample in this study are 100 consumers who have bought bakpia more than once in Bakpia Mutiara Jogja store. This research using simple regression analysis method. The results shows that flavor have a positive and significant influence on the purchasing decision of Bakpia Mutiara Jogja (sig = 0,000 0.05 and regression coefficient = 0.432).